The Silesian Piasts in chronicles - Skibiński, Edward (The Opole Studies in Administration and Law, 2016)
The paper contains an analysis of the vision of Silesia and the Silesian Piasts in our oldest historiography. The chronicles by Gall Anonymous, Master Vincent and Great Poland Chronicle are discussed succesively. Silesia in the narrative of the chronicles until testament Krzywoustego functions as an integral and important part of the Polish state. This is supported by the fact that it became a district of the princeps. Despite the expulsion of Władysław II coming back of his sons in the chronicle of Master Vincent is viewed as a positive step. They are not treated in the text as enemies to Kazimierz and Leszek the White. Their adherence to the camp Mieszko the Old stems rather from the ability of the latter to persuade people. This trend of Master Vincent’s chronicle is not maintained by the Great Poland chronicle. The Chronicler shows distinct dislikes of the Piasts of Silesia and their activities.